Perspectives on learning disabilities: Biological, cognitive, contextual - Sternberg, R.J.; Spear-Swerling, L. (Perspectives on Learning Disabilities: Biological, Cognitive, Contextual, 2018)
This book discusses biological, cognitive, educational, sociological, and interactive to discuss the nature of learning disabilities, its origins, its diagnosis, and effective remediation. It emphasizes the development of ideas as the motor forces behind the economic policies. © 1999 Taylor & Francis.
Keywords: dept.sed